2014
DOI: 10.1002/cam4.253
|View full text |Cite
|
Sign up to set email alerts
|

PAX1/SOX1 DNA methylation and cervical neoplasia detection: a Taiwanese Gynecologic Oncology Group (TGOG) study

Abstract: We aimed to determine whether PAX1/SOX1 methylation could be translated to clinical practice for cervical neoplasia detection when used alone and in combination with current cytology-based Pap screening. We conducted a multicenter case–control study in 11 medical centers in Taiwan from December 2009 to November 2010. Six hundred seventy-six patients were included in the analysis, including 330 in the training set and 346 in the testing set. Multiplex quantitative methylation-specific polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 55 publications
3
62
0
Order By: Relevance
“…These data revealed that the detection of PAX1 methylation has clinical diagnostic value in differentiating invasive CC, but may not be sufficient alone in screening for HSIL. A number of studies have indicated the potential value of PAX1 for the screening and detection of CC (49,51,52), in line with the findings of the present study, but the association between PAX1 and tumors requires further investigation. The present study used methylation-specific PCR to demonstrate that the PAX1 gene is abnormally methylated in cervical cancer specimens, with methylation rates as high as 87.5%, which is significantly different to those in normal cervical tissues and cervical precancerous lesions (49).…”
Section: Discussionsupporting
confidence: 90%
“…These data revealed that the detection of PAX1 methylation has clinical diagnostic value in differentiating invasive CC, but may not be sufficient alone in screening for HSIL. A number of studies have indicated the potential value of PAX1 for the screening and detection of CC (49,51,52), in line with the findings of the present study, but the association between PAX1 and tumors requires further investigation. The present study used methylation-specific PCR to demonstrate that the PAX1 gene is abnormally methylated in cervical cancer specimens, with methylation rates as high as 87.5%, which is significantly different to those in normal cervical tissues and cervical precancerous lesions (49).…”
Section: Discussionsupporting
confidence: 90%
“…The sensitivity of HPV DNA testing is satisfactory, whereas the high prevalence of transient HPV infections had limited the specificity of this approach (10,11). Currently, there are several test methods for HPV DNA assay, such as PCR, hybrid capture II (HC2), strip test (for E6 detection) as well as other novel techniques (5,(12)(13)(14)(15)34,35), Among these evaluation tools, PCR and HC2 tests remain the most commonly used techniques (34,35). Notwithstanding, single HPV DNA testing using PCR or HC2 method seems to yield inconstant results for the detection of cervical precancerous lesions (CIN2 or worse).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a recent study suggested that PAX1 methylation harbored a better diagnostic performance with a specificity of 0.88 when combined with sequential testing of HPV (14). In addition, the paneled assay of PAX1/SOX1 methylation has been previously described as well, which the sensitivity was greater than 0.70, and specificity greater than 0.90 (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Consequently, DNA methylation could be an effective biomarker for early diagnosis of cancers and prediction of prognosis in cancer patients. Previous studies showed the presence of aberrant DNA hypermethylation of classic tumor suppressor genes in cervical cancer; these genes include the paired box gene 1 (PAX1), 16 genes for sex-determining region Y-box 1, 17 epidermal growth factor receptor, cyclooxygenase-2, genes for protein tyrosine phosphatase receptor type R, 18 and zinc finger protein 582. 19 PAX1 shows the highest potential to be a methylation biomarker.…”
Section: Introductionmentioning
confidence: 99%